Streptogramin B biosynthesis in Streptomyces pristinaespiralis and Streptomyces virginiae: molecular characterization of the last structural peptide synthetase gene. - de Crécy-Lagard, V (1997)
Streptomyces pristinaespiralis and S. virginiae both produce closely related hexadepsipeptide antibiotics of the streptogramin B family. Pristinamycins I and virginiamycins S differ only in the fifth incorporated precursor, di(mono)methylated amine and phenylalanine, respectively. By using degenerate oligonucleotide probes derived from internal sequences of the purified S. pristinaespiralis SnbD and SnbE proteins, the genes from two streptogramin B producers, S. pristinaespiralis and S. virginiae, encoding the peptide synthetase involved in the activation and incorporation of the last four precursors (proline, 4-dimethylparaaminophenylalanine [for pristinamycin I(A)] or phenylalanine [for virginiamycin S], pipecolic acid, and phenylglycine) were cloned. Analysis of the sequence revealed that SnbD and SnbE are encoded by a unique snbDE gene. SnbDE (4,849 amino acids [aa]) contains four amino acid activation domains, four condensation domains, an N-methylation domain, and a C-terminal thioesterase domain. Comparison of the sequences of 55 amino acid-activating modules from different origins confirmed that these sequences contain enough information for the performance of legitimate predictions of their substrate specificity. Partial sequencing (1,993 aa) of the SnbDE protein of S. virginiae allowed comparison of the proline and aromatic acid activation domains of the two species and the identification of coupled frameshift mutations.